The economic burden of the postoperative management in surgically treated trauma patients with peri- and/or intra-articular fractures of the lower extremities: A prospective multicenter cohort study. Issue 2 (February 2022) - Kalmet, PHS; Andriessen, MT; Maduro, CV; van den Boom, N; Moens-Oyen, CPA; Hiligsmann, M; Janzing, H; van der Veen, A; Jaspars, C; Sintenie, JB; Seelen, HAM; Brink, PRG; et al.
Highlights: There is a substantial economic burden in monetary terms and effect on QoL of patients with peri‑ and/or intra-articular fractures of the lower extremities during 26 weeks follow-up. Total societal and healthcare costs are lower for the patients with a paid job relative to the patients without paid job. Rehabilitation time has a substantial impact on both ADL and QoL with improvement over time. Especialy for patients with a paid job in terms of utility. Abstract: Objectives: : To estimate the economic burden expressed in costs and quality of life of the post-surgical treatment of peri‑ and/or intra-articular fractures in the lower extremity from a societal perspective. Design: : This is a quantitative study as it aims to find averages and generalize results to wider populations. The design is a cost–of-illness and quality of life study focusing on costs (in euros), Activities of Daily Living (ADL) and Quality of Life (Qol) in patients with peri‑ and/or intra-articular fractures of the lower extremities. Setting: : Surgically treated trauma patients with peri‑ and/or intra-articular fractures of the lower extremities during 26 weeks follow-up. Patients were included from 4 hospitals in the Netherlands. Main outcome measures: : Costs, ADL and Quality Adjusted Life Years (QALY). Methods: : Cost of illness was estimated through a bottom-up method. The Dutch Eq-5D-5 L questionnaire was used to calculate utilities while Lower Extremity Functional Scale (LEFS) scores were used as a measure of ADL. Non-parametric bootstrapping was used to test for statistical differences in costs. Subgroup analyses were performed to determine the influence of work status and further sensitivity analyses were performed to test the robustness of the results. Results: : Total average societal costs were € 9836.96 over six months. Unexpectedly, total societal and healthcare costs were lower for patients with a paid job relative to patients without. Sensitivity analyses showed that our choice of a societal perspective and the EuroQol as our primary utility measurement tool had a significant effect on the outcomes. The ADL at baseline was respectively; 10.4 and at 26 weeks post-surgery treatment 49.5. The QoL was at baseline respectively; 0.3 and at 26 weeks post-surgery treatment 0.7. These findings are indicative of a significantly improved ADL and QoL ( p ≤ 0.05) over time. Conclusions: : This study reveal a substantial economic burden in monetary terms and effect on QoL of patients with peri‑ and/or intra-articular fractures of the lower extremities during 26 weeks follow-up. Registration: : This study was registered in the Dutch Trial Register (NTR6077). Date of registration: 01–09–2016.